Foundations of public law - Loughlin, Martin (Oxford : Oxford University Press, 2010)
This text develops Martin Loughlin's distinctive and provocative theory of public law. Tracing the historical evolution of the concept of public law, the book rethinks the foundational concepts of state, constitution, and government, arguing that public power is created, not controlled, by law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public law; Public law -- History; Public law -- Philosophy